Association Study of TAF1 Variants in Parkinson’s Disease - Zeng, Qian; Pan, Hongxu; Zhao, Yuwen; Wang, Yige; Xu, Qian; Tan, Jieqiong; Yan, Xinxiang; Li, Jinchen; Tang, Beisha; Guo, Jifeng (Frontiers in Neuroscience, 2022)
Increasing evidence reveals sex as an important factor in the development of Parkinson's disease (PD), but associations between genes on the sex chromosomes and PD remain unknown. TAF1 is a gene located on the X chromosome which is known to cause X-linked syndromic mental retardation-33 (MRXS33) and X-linked Dystonia-Parkinsonism (XDP). In this study, we conducted whole-exome sequencing (WES) among 1,917 patients with early-onset or familial PD and 1,652 controls in a Chinese population. We detected a hemizygous frameshift variant c.29_53dupGGA(CAG)2CTACCATCA(CTG)2C (p.A19Dfs*50) in two unrelated male patients. Further segregation analysis showed an unaffected family member carried this variant, which suggested the penetrance of the variant may be age-related and incomplete. To verify the effects of TAF1 on PD, genetic analyses were carried separately by gender. Analysis of rare variants by optimal sequence kernel association (SKAT-O) test showed a nominally significant difference in variant burden between the male PD patients and controls (2.01% vs. 1.38%, p = 0.027). In the female group, none of the variant types showed significant association with PD in this study. In conclusion, we found rare variants in TAF1 may be implicated in PD, but further genetic and functional analyses were needed.